PENERAPAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELASIV SDN 002 AIR MOLEK I KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Sri Romadona; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPS'S studying student brazes IV. SDN 002 i. Beauteous Waters one has reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 36 students which reach points according to KKM as much 15 students with averagely brazes 63,75. Its low is yielding studies it at causes since teacher be still dominate deep learning so student involvement in learning becomes less active. Base about problem research do that action brazes with learnings model implement Numbered Head Together (NHT). This research intent to increase IPS'S studying result student brazes IV. SDN 002 I. Beauteous Waters School Years 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Learning Numbered Head Together (NHT), therefore gets to increase IPS'S studying result student brazes IV. SDN 002 i. Beauteous Waters on technological formative material production, communication and transportation. It can at see of thoroughness result studies individual and klasikal which gotten by student on base score which is with thoroughness percentage 41,67%, with average 63,75, worked up on i. cycle with thoroughness percentage 66,67% by average 67,5. Worked up again on cycle II.which is with thoroughness percentage 88,89% by average 77,64. On Activity learns first cycle with percentage average 77% worked up as 92% on second cycle. Student activity on first cycle with percentage average 73% worked up as 92% on second cycle.Of acquired data as above as gets to be known that pass through learning model Implement Numbered Head Together (NHT), can increase IPS'S studying result student brazes IV. SDN 002 I. Beauteous WatersKey word : Numbered Head Together , IPS'S Learned result